2007
DOI: 10.1007/s11249-006-9190-9
|View full text |Cite
|
Sign up to set email alerts
|

Study of surface films of crystalline and amorphous overbased sulfonates and sulfurized olefins by X-ray absorption near edge structure (XANES) spectroscopy

Abstract: In the past large synergistic effects have been reported for combinations of overbased sulfonate and sulfurized olefin in four-ball EP testing. In this study, we examined the effect of crystallinity on the formation of the tribofilms using X-ray absorption near edge structure (XANES) spectroscopy. Using this technique, we were able to differentiate the carbonate from organic carbon in C K-edge spectra, as well as, determining the difference between FeS, FeS 2, RSO 3 ) , and SO 4 2) in the sulfur spectra. While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Estimated values include 80 nm [18], 240 nm [20] and 1 lm [17] while a recent XANES study has found that the films formed by simple solutions of OBCaSu detergents in a four-ball test were very thin and less than 10 nm [21]. It is thus likely that the film thickness depends strongly on the test operating conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Estimated values include 80 nm [18], 240 nm [20] and 1 lm [17] while a recent XANES study has found that the films formed by simple solutions of OBCaSu detergents in a four-ball test were very thin and less than 10 nm [21]. It is thus likely that the film thickness depends strongly on the test operating conditions.…”
Section: Introductionmentioning
confidence: 98%
“…Related research carried out by Normand et al [7] showed that the calcium carbonate overbased micelles, when used as an additive, undergo structural and physic-chemical changes during the build-up of the interfacial tribofilm. Costello et al [2] confirmed the existence of calcium carbonate in the surface tribofilms from both amorphous overbased calcium sulfonates (AOBCSs) and crystalline overbased calcium sulfonates (COBCSs) through XANES studies. Similar results have also been reported by Kubo et al [1].…”
Section: Introductionmentioning
confidence: 96%
“…Over the past few decades, overbased sulfonates have been found to be excellent antiwear (AW) additives, forming boundary protective films due to the decomposition of the amorphous inorganic carbonate on metal surfaces in sliding parts [2,3]. The introduction of calcium carbonate with overbased sulfonates into lubricating oil or grease can also improve the load-carrying capacity and friction-reducing property of the base oil/grease [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Polysulfide is one of the most widely used extreme pressure (EP) additives that can prevent the rubbing surfaces from seizure and prolong the life of the equipment. In the past decades, the study of disulfides and sulfurised olefins used as EP additives has been well documented, and their tribological mechanisms have been investigated . Most of the researches only focused on the EP property, while polysulfides can be also found to be beneficial to the anti‐wear property .…”
Section: Introductionmentioning
confidence: 99%
“…As many researchers demonstrated, X‐ray absorption near‐edge structure (XANES) spectroscopy is an effective method for investigating the chemistry of films generated from lubricating process . In this paper, XANES has been introduced to analyse both of the thermal and tribofilms generated from three polysulfides with/without a hindered phenol in MO and DE.…”
Section: Introductionmentioning
confidence: 99%